Chemotherapeutic drug sensitivity of primary cultures of epithelial ovarian cancer cells from patients in relation to tumour characteristics and therapeutic outcome. (February 2014) - von Heideman, Anne; Tholander, Bengt; Grundmark, Birgitta; Cajander, Stefan; Gerdin, Eva; Holm, Leif; Axelsson, Agneta; Rosenberg, Per; Mahteme, Haile; Daniel, Erika; Larsson, Rolf; Nygren, Peter
Abstract Background. A number of chemotherapeutic drugs are active in epithelial ovarian cancer (EOC) but so far choice of drugs for treatment is mostly empirically based. Testing of drug activity in tumour cells from patients might provide a rationale for a more individualised approach for drug selection. Material and methods. Sensitivity of EOC to chemotherapeutic drugs was analysed in 125 tumour samples from 112 patients using a short-term primary culture assay based on the concept of total cell kill. Sensitivity was related to tumour histology, treatment status and clinical tumour response. Results. For most EOC standard drugs serous high grade and clear cell EOC were the most sensitive subtypes and the mucinous tumours the most resistant subtype. Docetaxel, however, tended to show the opposite pattern. Samples from previously treated patients tended to be more resistant than those from treatment naïve patients. The activity of cisplatin correlated with that of other drugs with the exception of docetaxel. Tumour samples from two sites in the same patient at the same occasion showed similar cisplatin sensitivity in contrast to samples taken at different occasions. Samples from patients responding in the clinic to treatment were more sensitive to most drugs than samples from non-responding patients. At the individual patient level, drug sensitivity in vitro compared with clinical response showed sensitivities and specificities in the 83–100% and 55–83% ranges, respectively. Conclusions. Assessment of EOC tumour cell drug sensitivity in vitro provides clinically relevant and potentially useful information for the optimisation of drug treatment.